Job matching system for IT students using fuzzy logic / Dalilah Masngon - Masngon, Dalilah (2020)
Job matching is a process of assigning a person to find a suitable job based on several criteria of the applicants. Nowadays, most applicants or students do not know how to get a suitable job based on their field and skills. Furthermore, many students choose their job path without receiving proper advice from the professional or university services. This is potentially cause mismatch between academic achievements, personality, interest and abilities of the students towards the job. Therefore, the aim of this study is to match the job system for IT students using fuzzy logic technique based on personality and skills. This study is conducted based on Agile Methodology that consists of five phases, which are Planning, Design, Development, Testing and Evaluate. The system has been tested using Usability Testing and Functionality Testing. The results from the testing shows that the system can produce a reliable suggestion of suitable job for the students based on the fuzzy logic approach.